2007
DOI: 10.1016/j.actamat.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Two types of S phase precipitates in Al–Cu–Mg alloys

Abstract: Transmission electron microscopy (TEM) and differential scanning calorimetry (DSC) have been used to study S phase precipitation in an Al-4.2Cu-1.5Mg-0.6Mn-0.5Si (AA2024) and an Al-4.2Cu-1.5Mg-0.6Mn-0.08Si (AA2324) (wt.%) alloy. In DSC experiments on as solution treated samples two distinct exothermic peaks are observed in the range 250-350°C, whereas only one peak is observed in solution treated and subsequently stretched or cold worked samples. Samples heated to 270°C and 400°C at a rate of 10°C/min in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(151 citation statements)
references
References 25 publications
7
142
0
2
Order By: Relevance
“…This approach appears unsuited for the S phase formation, as recent work indicates that S phase does not have a precursor phase that is consumed during S phase formation [29,56]. (In particular, the Ѕ΄ precipitates are essentially S phase with a slightly different orientation ratio [56] and Ѕ˝ phase does not appear to transform into S phase [30]. It is also noted that neither of the two approaches discussed will in itself reduce the number of parameters to be fitted.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This approach appears unsuited for the S phase formation, as recent work indicates that S phase does not have a precursor phase that is consumed during S phase formation [29,56]. (In particular, the Ѕ΄ precipitates are essentially S phase with a slightly different orientation ratio [56] and Ѕ˝ phase does not appear to transform into S phase [30]. It is also noted that neither of the two approaches discussed will in itself reduce the number of parameters to be fitted.…”
Section: Resultsmentioning
confidence: 97%
“…Other researchers [35] have suggested that in the Al-Zn-Mg-Cu system a transformation from a well-defined precursor phase, η', to η, with the interfacial energy of the precursor much lower than that of η, can provide an accurate model. This approach appears unsuited for the S phase formation, as recent work indicates that S phase does not have a precursor phase that is consumed during S phase formation [29,56]. (In particular, the Ѕ΄ precipitates are essentially S phase with a slightly different orientation ratio [56] and Ѕ˝ phase does not appear to transform into S phase [30].…”
Section: Resultsmentioning
confidence: 99%
“…The faint streaks with maximum intensities near the 1/2{200} α positions (arrows in the SAED shown in Fig. 8b) can result from Cu þMg-rich GPB (Guinier-Preston-Bagaryatsky) zones precipitated in Al-Cu-Mg alloys during early stages of natural aging [11,12,[30][31][32][33][34]. However, no unambiguous evidence for the formation of the GPB zones was obtained under tension followed by natural aging.…”
Section: Precipitation Behavior During Pre-strainingmentioning
confidence: 90%
“…(Mg-Cu co-clusters can not be resolved in TEM, but can be resolved by 3 dimensional atom probe [29,46,47].) Although the HPT processed Al-1Mg-4Cu alloy has a high dislocation density which might stimulate nucleation of semicoherent precipitates (S or S' phase [14,48]), no such precipitates were observed in the aged Al-1Mg-4Cu sample. Hence the Cu-Mg clusters played an important role in strengthening of Al-1Mg-4Cu subjected to HPT.…”
Section: The Evolution Of Microstructure In Pure Al During Hptmentioning
confidence: 99%